Intraoperative Cell-Saver Caused More Autologous Salvage Hemolysis in a Hereditary Spherocytosis Patient Than in a Normal Erythrocyte Patient - Jin, Di; Shen, Le; Huang, Yuguang (Frontiers in Physiology, 2022)
Hereditary spherocytosis is a common red blood cell disease caused by an inherited red blood cell membrane defect, leading to a spherical shape and propensity for hemolysis. There is a lack of reports on intraoperative autologous blood transfusion for hereditary spherocytosis patients. We hereby report our recent experience with using the Cell Saver® system for intraoperative red blood cell salvage on a hereditary spherocytosis patient. There was a drastic increase in salvaged blood free-hemoglobin compared with the preoperative sample (82.6 mg/dl vs. 6.2 mg/dl) which indicated severe hemolysis. Although our patient recovered smoothly with a normal liver and renal function test and reported no adverse reaction during follow-up, it is noteworthy that severe hemolysis could happen during the cell salvage process for patients with hemolytic anemia, as there are similar reports on sickle cell anemia, beta-thalassemia intermedia, and paroxysmal nocturnal hemoglobinuria. Therefore, more clinical attention and thorough research should be drawn into this perspective, namely, hemolysis during the red blood cell salvage process for patients with hemolytic anemia.